2015
DOI: 10.1016/j.bbmt.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Outcome of Allogeneic Transplantation in IgD and Nonsecretory Myeloma. A Report on Behalf of the Myeloma Subcommittee of the Chronic Malignancies Working Party of the European Group for Blood and Marrow Transplantation

Abstract: We have recently reported on the outcome of autologous transplantation in the rare myelomas (IgD, IgE, IgM, and nonsecretory [NS]) but there is no real information on the outcome of these conditions after allogeneic transplantation. We used the European Group for Blood and Marrow Transplantation myeloma database to compare the outcomes after allogeneic transplantation of 1354 common myelomas (IgG, IgA, and light chain myeloma) with the outcome in 26 IgD myelomas and 52 NS myelomas. There was little difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…43 Allogeneic hematopoietic cell transplantation, which utilizes an alloimmune reaction against MM (GVM effect), has emerged as an alternative treatment option, with possible prolonged MM control and curative potential, in these patients. [12][13][14][15][16][17][18][19][20][21] The existence of GVM effect was demonstrated directly in patients who received DLI for MM relapse after Allo-HCT. [16][17][18] DLI was shown to induce complete and partial response in 40-55% of these patients, with accompanying acute and chronic GVHD rates of 55-57% and 26-47%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…43 Allogeneic hematopoietic cell transplantation, which utilizes an alloimmune reaction against MM (GVM effect), has emerged as an alternative treatment option, with possible prolonged MM control and curative potential, in these patients. [12][13][14][15][16][17][18][19][20][21] The existence of GVM effect was demonstrated directly in patients who received DLI for MM relapse after Allo-HCT. [16][17][18] DLI was shown to induce complete and partial response in 40-55% of these patients, with accompanying acute and chronic GVHD rates of 55-57% and 26-47%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9][10][11] Allogeneic hematopoietic cell transplantation (Allo-HCT) has been explored in advanced MM as a curative option through a graft-versus-myeloma (GVM) effect. [12][13][14][15][16][17][18][19][20][21] The existence of a GVM effect was demonstrated following the observation of complete responses after donor lymphocyte infusion (DLI) and withdrawal of immunosuppression in patients with MM relapsing after Allo-HCT. [16][17][18] Unfortunately, conventional myeloablative conditioning is associated with an unacceptably high early treatment-related mortality (TRM) of up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Although the precise causes of renal dysfunction in our patients with oligosecretory myeloma in our study were not defined, there was a high frequency of IgD MM, consistent with prior reports of shorter OS and higher frequency of renal dysfunction. 22,23 We also analyzed the cytogenetic characteristics in patients with unmeasurable and measurable MM, and found that patients with unmeasurable disease were more commonly t (11;14). Other factors such as ploidy, del(17p), del(13p), 1q21 gains, t(4;14), and t (14;16) were not significantly different between patients with measurable and unmeasurable disease.…”
Section: Discussionmentioning
confidence: 99%
“…As a most severe type among all the subtypes of MM, immunoglobulin D multiple myeloma (IgD MM) is very rare comprising only 1 to 2% of all MM cases featured by diagnosis in relatively young patients, and often accompanied by multiple adverse prognosis, such as extraosseous lesions, renal failure, extramedullary involvement, amyloidosis [4,5]. The most distinguish characteristic of lgD MM is poor outcome of refractory status, only 13 ~ 21-month overall survival (OS) compared with 3 ~ 6-year overall median survival in common MM [6][7][8]. Therefore, systemic investigation on IgD MM is purposeful to reveal the recurrent and refractory features in both IgD and other types of MM, and beneficial to develop potent therapeutic strategy on MM.…”
Section: Introductionmentioning
confidence: 99%